2011
DOI: 10.1051/0004-6361/201117670
|View full text |Cite
|
Sign up to set email alerts
|

Angle-dependent radiative grain alignment

Abstract: Context. Interstellar grain alignment studies are currently experiencing a renaissance due to the development of a new quantitative theory based on radiative alignment torques (RAT). One of the distinguishing predictions of this theory is a dependence of the grain alignment efficiency on the relative angle (Ψ) between the magnetic field and the anisotropy direction of the radiation field. In an earlier study we found observational evidence for such an effect from observations of the polarization around the sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 33 publications
10
44
0
Order By: Relevance
“…• periods and the good agreement between angular peaks at 100 and 350 µm we find strong evidence for a detection of the predicted angular dependence of RATs This work, taken together with the optical work towards HD 97300 (Andersson et al 2011), provides the best current tests of the RAT-predicted angular alignment dependence.…”
Section: Based On the Low Faps For 180supporting
confidence: 67%
See 1 more Smart Citation
“…• periods and the good agreement between angular peaks at 100 and 350 µm we find strong evidence for a detection of the predicted angular dependence of RATs This work, taken together with the optical work towards HD 97300 (Andersson et al 2011), provides the best current tests of the RAT-predicted angular alignment dependence.…”
Section: Based On the Low Faps For 180supporting
confidence: 67%
“…The analysis presented here can also be applied to the optical polarization data around the star HD 97300, where Andersson et al (2011) found a strong signal and peak alignment efficiency within 10…”
Section: Periodogramsmentioning
confidence: 91%
“…Such a phenomenon is reported in the diffuse interstellar medium around a bright star (e.g., Andersson & Potter 2010;Andersson et al 2011), and a similar mechanism may work in the environment with a lack of radiation produced by the starless core. The linearity in the P H versus H K s -relationship cannot reject the possibility of the mechanism, because the radiative torque effect is an angular one.…”
Section: C Fittingmentioning
confidence: 53%
“…The uncertainty on the intrinsic color is directly linked to the spectral type uncertainty. The latter is assumed to be of one sub-class consistent with other work (Andersson et al 2011;Torres et al 2006). In the case of stars with only the effective temperature, its uncertainty comprises the uncertainty on the spectral type.…”
Section: Reddening Turn-on Distancementioning
confidence: 93%